PENERAPAN MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DALAM PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA KELAS V SD - Afif Amroellah (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
Application of cooperative learning models type Student Teams Achievement Divisions (STAD) in the improved motivation and learning outcomes science Student fifth grade Elementary School. The purpose f this study is to describe the steps for implementing the model type Student Cooperative Learning Teams Achievement Divisions (STAD) and improve motivation and learning outcomes elementary fifth grade science students. This research is a classroom action research (PTK) collaborative. Research carried out in three cycles, with each cycle consisting of pe-planning, action, observation, and reflection. The subjects were students of fifth grade SDN 6 Dawuhan Situbondo totaling 28 students consisting of 15 male students and 13 female students. The results showed that the model of cooperative learning type Student Teams Achievement Divisions (STAD) can improve motivation and learning outcomes elementary fifth grade science students